NUTRITIONAL SPECTRUM OF SAP OF TREES AND SHRUBS OF FERGANA REGION - Ganiyev Komolidin Xalilovich; Mirzaliev Abdujabbor Mamatyusuf ugli; Oxunjonova Nigora Shamsiddinovna (American Journals, 2022)
In the article, aphids live in 48 species of trees and shrubs belonging to 19 families and 32 families in the territory of Fergana city, classification-quantitative indicators of representatives of trees and shrubs affected by aphids, the nutritional spectrum of aphids in the Fergana region are analyzed. it is reported that the indicator is at the highest level in the genus Aphis, and its species live in representatives of 9 families of plants.
Keywords: Rosaceae, Salicaceae, Capripholiaceae), Bignoniaceae, Cupressaceae, Pinaceae, Saxifragaceae, Aphis L, Dendrоfil.